2016
DOI: 10.1017/s0025315416001387
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of the genusHyalopecten(Bivalvia: Pectinidae) from the abyssal and hadal zones of the North-western Pacific Ocean

Abstract: Three new species, Hyalopecten vityazi sp. nov., H. abyssalis sp. nov. and H. kurilensis sp. nov., are described from the abyssal and hadal zones of the North-western Pacific. Hyalopecten vityazi was found in the Kuril-Kamchatka and Aleutian trenches at 6090–8100 m depth. It is the most deep-water species of the order Pectinida. Hyalopecten abyssalis and H. kurilensis were found at the abyssal plain adjacent to the Kuril-Kamchatka and Aleutian trenches at 4550–5045 m depth. To date, 13 species of the genus Hya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In recent years, international expeditions organized by the Russian Federation and Germany have sampled the deep-sea benthic fauna in an extensive region of the northwestern Pacific Ocean with depths greater than 3,000 m. The studies were focused on the composition and distribution of the benthic fauna in the deep-sea basins of the Seas of Japan and Okhotsk, the Kuril-Kamchatka Trench, and at the abyssal plain of the Pacific Ocean adjacent to the Kuril-Kamchatka Trench ( Malyutina & Brandt, 2013 ; Brandt & Malyutina, 2015 ; Malyutina, Chernyshev & Brandt, 2018 ; Brandt et al, 2019 ). Benthic macrofauna rich in species number and abundance was found in these deep-sea ecosystems, with bivalves being one of the dominant groups of animals ( Brandt et al, 2013 , 2015 , 2018 , 2020 ; Kamenev, 2013 , 2014 , 2015 , 2018a , 2018b , 2018c , 2019 ; Kamenev et al, 2022 ). Among the bivalve fauna of all the studied deep-sea areas of the northwestern Pacific Ocean, the Thyasiridae was the most species-rich family and many thyasirids were the dominant species in terms of abundance in the benthic macrofaunal communities ( Kamenev, 2013 , 2015 , 2018a , 2019 ; Kamenev et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, international expeditions organized by the Russian Federation and Germany have sampled the deep-sea benthic fauna in an extensive region of the northwestern Pacific Ocean with depths greater than 3,000 m. The studies were focused on the composition and distribution of the benthic fauna in the deep-sea basins of the Seas of Japan and Okhotsk, the Kuril-Kamchatka Trench, and at the abyssal plain of the Pacific Ocean adjacent to the Kuril-Kamchatka Trench ( Malyutina & Brandt, 2013 ; Brandt & Malyutina, 2015 ; Malyutina, Chernyshev & Brandt, 2018 ; Brandt et al, 2019 ). Benthic macrofauna rich in species number and abundance was found in these deep-sea ecosystems, with bivalves being one of the dominant groups of animals ( Brandt et al, 2013 , 2015 , 2018 , 2020 ; Kamenev, 2013 , 2014 , 2015 , 2018a , 2018b , 2018c , 2019 ; Kamenev et al, 2022 ). Among the bivalve fauna of all the studied deep-sea areas of the northwestern Pacific Ocean, the Thyasiridae was the most species-rich family and many thyasirids were the dominant species in terms of abundance in the benthic macrofaunal communities ( Kamenev, 2013 , 2015 , 2018a , 2019 ; Kamenev et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of these expeditions was to study the species composition and distribution patterns of bottom animals, as well as to assess the faunal relationships in the deep-sea ecosystems of the Sea of Okhotsk and the Kuril-Kamchatka Trench separated by such a natural barrier as the Kuril Islands Brandt et al, 2019). As a result, numerous species from different taxonomic groups of animals were described, the composition of macro-and meiofauna and the patterns of distribution of the main taxonomic groups of animals were studied, the faunal relationship and levels of endemism of these deep-sea areas were estimated (e.g., Maiorova, 2018, 2019;Alalykina, 2018;Brandt et al, 2018Brandt et al, , 2019Polyakova, 2018, 2019;Fukumori et al, 2018Fukumori et al, , 2019Kamenev, 2018aKamenev, ,b, 2019Kamenev, , 2020Maiorova and Adrianov, 2018a,b;Brandt, 2018, 2020;Mironov et al, 2018Mironov et al, , 2019bBorisanova and Chernyshev, 2019;Brandão et al, 2019;Mordukhovich et al, 2019;Schmidt et al, 2019;Alalykina and Polyakova, 2020;Maiorova and Adrianov, 2020;Saeedi and Brandt, 2020). However, the analysis of the quantitative distribution of macro-and meiofauna in the Kuril Basin has not been completed, and only preliminary results of the macrofauna abundance study have been reported for the Kuril-Kamchatka Trench (Lins and Brandt, 2020).…”
Section: Introductionmentioning
confidence: 99%